The Role of Rubella Virus Infection among Women with Spontaneous Abortion in Al-Najaf Governorate - Elham Jawad Kadhum (International Journal of Virus Studies, 2026)
Rubella virus could cause a spectrum of birth defects known as Congenital Rubella Syndrome (CRS) if the infection occurs within the first or second trimester of pregnancy. Repeated miscarriage is defined as a condition with two or more consecutive abortions before the 20–25 weeks of gestation. Rubella remains to be a severe public health problem in developing countries. Recurrent miscarriage is a multi-factorial disease, which occurs in approximately 1%–2% of women at the reproductive age (Sebastian D et al., 2008). The present study was aimed to determine the Sero-prevalence of rubella infection among women with spontaneous abortion in Al-Najaf city. In this study, obtained blood samples from a total of 205 women with spontaneous abortion were enrolled from Al-Zahraa Hospital for childbirth and children in AL-Najaf Governorate/Iraq between August 2024 and January 2025. From the women aged 14–43 years, the sera were collected and stored at –80°C until uses. Rubella virus infection was diagnosed by the detection of rubella specific IgM, IgG antibodies using indirect Enzyme Linked Immunosorbent Assay (ELISA) as per manufacturer’s instructions. Data were analyzed by using SPSS version 21. The Rubella virus infection is one of the recurrent abortion causes among pregnant women in our community. In this study, 205 blood samples were collected from women with spontaneous abortion in period between August (2024) and January (2025) from obstetrics and gynecology hospital in Al-Najaf Al Ashraf governorates. The investigation was done by ELISA technology using immunological kits for demonstration of IgG, IgM antibody. Current study showed the existence of Rubella-IgM antibody by 78% compared to 22% detection of Rubella IgG antibody with significant differences. The result demonstration in Figures 1 and 2 shows that once test done in Kufa University Laboratories to give presumptive diagnosis and repeated test after 7–14 days for confirmative identification because of commonly Iraqis carry antibody for these causes and this provide overlapping results (3). This result indicated the Rubella virus infection is acute and recent. Also, the results revealed that the highest rate of miscarriage in women was within the age group (20–25) years by 32%, while the age group (37–32) years gave the lowest percentage where it was 12%, as well as the results of the study showed that 61% of Women had miscarriages in the first trimester of pregnancy. The results displayed that there were significant differences in the number of aborted women in favor of urban areas than in rural areas. Conclusion: According to the results of our research, Rubella virus is considered one of the main causes of spontaneous abortion in the province of Najaf in Iraq. This study also reveals the abortion occur in first trimester of pregnancy and then reduce in second and third trimester of pregnancy women in Iraq.
Keywords: Eliza; IgG antibody; Rubella virus; disease; recurrent abortion